2014
DOI: 10.1007/s10853-014-8572-x
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the structural, electronic, and magnetic properties of Fe2−x Ti x O3/Fe2O3 thin films with x = 0.44 grown on Al2O3 (0001)

Abstract: The interface between hematite (a-Fe 2 III

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In fact, the intensity ratio of the Fe L 3 /L 2 peaks can be used as an indicator of the Fe oxidation state. High ratios (5–7) indicate Fe in higher oxidation states (+II–+IV); low ratios (4 and below) reduced/metallic Fe. , The Fe L 3 /L 2 peak ratio along the profile is therefore highlighted in the right side of panel B. Oxidized iron is thus only found at the particle edges (and within the perovskite bulk), metallic iron in the rod center. Note that this can be also indirectly derived from the internal HAADF contrast of the iron rod: as the HAADF intensity is mostly dominated by the average atom number, oxygen-rich areas are darker than iron-rich ones, and in turn, the oxygen concentration is highest along the rod edge.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the intensity ratio of the Fe L 3 /L 2 peaks can be used as an indicator of the Fe oxidation state. High ratios (5–7) indicate Fe in higher oxidation states (+II–+IV); low ratios (4 and below) reduced/metallic Fe. , The Fe L 3 /L 2 peak ratio along the profile is therefore highlighted in the right side of panel B. Oxidized iron is thus only found at the particle edges (and within the perovskite bulk), metallic iron in the rod center. Note that this can be also indirectly derived from the internal HAADF contrast of the iron rod: as the HAADF intensity is mostly dominated by the average atom number, oxygen-rich areas are darker than iron-rich ones, and in turn, the oxygen concentration is highest along the rod edge.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of corundum thin films on α-Al 2 O 3 (0001) has been reported in several experimental studies exploiting different techniques such as molecular beam epitaxy [49,50,51], pulsed laser deposition [52], helicon plasma- [53] or r.f. magnetron sputtering [54].…”
Section: Discussionmentioning
confidence: 99%
“…only X and Al ions, instead of three or four different cations in a perovskite superlattice). Several studies have reported the successful growth of corundum thin films on α-Al 2 O 3 (0001) using molecular beam epitaxy [53][54][55] , pulsed laser deposition 56 , helicon plasma-57 or r.f. magnetron sputtering 58 .…”
Section: Discussionmentioning
confidence: 99%